Semiotics and Its Application in Pohutu Aadati Lihu Lo Limu Devices in Gorontalo - Sance A. Lamusu (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article is a preliminary research on pohutu aadati lihu lo limu, ‘customary ceremonial devices of lemon bath’ which focuses on sign and sign system f language existing in the cultural device. It can be concluded that there are sign and sign system of language based on relation between expression and content (ERC) and sign system of language which is based on the relation of reality and its basic kinds such as icons, indices, and symbols ([R]-[O]-[ I]. Sign and sign system [E]- [R]-[C] have forms like [R] between E and C: that the development of meaning and change to the secondary or connotative direction [C] only once occurs in expression [E] = (E-R-C); in case the event the development of meaning and change to the secondary or connotative direction [C] occurs several times (6x) in the expression [E], the form will be like the relation of [R] E(E-R1-C; E-R2-C; E-R3-C; E-R4-C; E-R5-C; E-R6-C] C. The meaning development of such form of sign and sign system both at the level of first-primary (denotative) and the level of second-secondary (connotative) occurs several times in [E]. It can be said that the meaning development at the level of first-primary (denotative) is synonymous with form indices and icons and the meaning development at the level of second-secondary (connotative) is synonymous with symbols.